2022
DOI: 10.1038/s41598-022-16641-1
|View full text |Cite
|
Sign up to set email alerts
|

Detection of NO3− introduced in plasma-irradiated dry lettuce seeds using liquid chromatography-electrospray ionization quantum mass spectrometry (LC-ESI QMS)

Abstract: Discharge plasma irradiates seeds with reactive oxygen and nitrogen species (RONS). However, RONS introduced in seeds by plasma irradiation have not been successfully detected thus far. This study provides experimental evidence that nitrate ion NO3− is introduced in lettuce seeds as RONS upon irradiation with atmospheric-pressure air dielectric barrier discharge plasma. Plasma irradiation for 5 min promotes seed germination. The components of the plasma-irradiated seeds were examined using electrospray ionizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 48 publications
1
9
0
Order By: Relevance
“…The reactive oxygen and nitrogen species (RONS) formed in plasma are involved in a variety of seed processes, including maturation, ageing, and germination, followed by seedling growth [33,34]; however, the uptake of RONS from plasma by seeds was not detected until recently. RONS introduction to seeds by similar DBD plasma as used in this study was recently demonstrated by Okumura et al [35]. The study provided experimental evidence obtained by LC-MS that nitrate ion NO 3 − is introduced in lettuce seeds as RONS upon irradiation with atmospheric pressure air DBD plasma.…”
Section: Discussionsupporting
confidence: 72%
“…The reactive oxygen and nitrogen species (RONS) formed in plasma are involved in a variety of seed processes, including maturation, ageing, and germination, followed by seedling growth [33,34]; however, the uptake of RONS from plasma by seeds was not detected until recently. RONS introduction to seeds by similar DBD plasma as used in this study was recently demonstrated by Okumura et al [35]. The study provided experimental evidence obtained by LC-MS that nitrate ion NO 3 − is introduced in lettuce seeds as RONS upon irradiation with atmospheric pressure air DBD plasma.…”
Section: Discussionsupporting
confidence: 72%
“…Recently, atmospheric-pressure plasma has been intensively investigated for biomedical [1][2][3][4] , such as the inactivation of bacteria including antibiotic-resist germs, fungi, spores or viruses and the hemostasis [5][6][7][8] , and agricultural applications [9][10][11][12] , such as germination enhancement, subsequent growth improvement and DNA methylation alterations of plant seeds [13][14][15] . Hence, the plasma irradiation can be applied in medical and agricultural treatments.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] However, gene expression and phytohormone content analysis recently revealed that plasma affects germination-related factors. [14][15][16][17][18] On the other hand, due to the growing expectation for plant breeding by genome editing, molecular transfer into plant cells by plasma treatment has also been reported. Our group has established the microplasma method as a gene and molecule transfection technology in animal cells, [19][20][21][22][23][24][25][26] and its application in plant cells is under investigation.…”
Section: Introductionmentioning
confidence: 99%